2017
DOI: 10.1515/jbcpp-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single or combined administration of salmon calcitonin and omega-3 fatty acids vs. diclofenac sodium in sodium monoiodoacetate-induced knee osteoarthritis in male Wistar rats

Abstract: Background: There is a continuous search for a better therapy in osteoarthritis (OA) management. Therefore, this study investigated the effects of salmon calcitonin (Sct) and/or omega-3 fatty acids (N-3) relative to diclofenac sodium (DF) in induced knee osteoarthritic male Wistar rats. Methods:The 40 rats that were used in this study were divided into 8 groups (n = 5 rats), viz: Normal control; OA control; OA + N-3; OA + Low dose of Sct (Sct.Lw); OA + High dose of Sct (Sct.Hi); OA + N-3 + SCt.Lw; OA + N-3 + S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It has been documented that supplementation with N-3 at a high dose could be accompanied with some unfavorable events [ 35 ]. The noted anti-inflammatory effects of N-3 [ 36 ] in this study could be attributed to their metabolites, such as, resolvins [ 37 ], neuroprotectin-D1 and docosatrienes [ 38 , 39 ]. Resolvin D1, resolvin E1, and protectin D1 inhibits transendothelial migration of neutrophils into sites of inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…It has been documented that supplementation with N-3 at a high dose could be accompanied with some unfavorable events [ 35 ]. The noted anti-inflammatory effects of N-3 [ 36 ] in this study could be attributed to their metabolites, such as, resolvins [ 37 ], neuroprotectin-D1 and docosatrienes [ 38 , 39 ]. Resolvin D1, resolvin E1, and protectin D1 inhibits transendothelial migration of neutrophils into sites of inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…Knee OA was induced according to previous protocols [5, 14]. Briefly, 4 mg of MIA were dissolved in 40 μL of sterile saline and this volume of solution was injected intraarticularly through the patellar ligament of the left knee joint of each rat that had been anesthetized using 50 mg/kg sodium pentobarbital by intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%
“…OA can affect the hand, spine, hip, wrist and ankle. However, knee OA represents the most widespread form of this disease [5]. Although, there are various therapeutic methods for OA, such as surgery, drug and adjuvant therapy, it is difficult to completely stop the development of OA, which results in continuous pain and even long-term disability [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ferrándiz et al demonstrated that IL-1β level in 2-month-old ACLT rats was significant higher than that of sham-operated rats from ~ 110 to ~ 200 pg/mL 11 . Measurements of bone turnover markers revealed that knee OA was associated with increased c-telopeptide of type 1 collagen (CTX-1) and alkaline phosphatase levels 26 . We thus hypothesized that OA from ACLT would lead to bone loss in both local sites (i.e., tibiae) and distant sites (i.e., vertebrae).…”
Section: Discussionmentioning
confidence: 99%